Molecular Epidemiology of Carbapenem-Resistant Enterobacter cloacae in a University Hospital in Japan - Tetsuka, Nobuyuki (Open Forum Infect Dis, 2017)
BACKGROUND: Carbapenem-resistant Enterobacteriaceae (CRE) is becoming more significant concerns in the clinical settings. National surveillance for CRE in Japan has started since September 2014 under the criteria of either cefmetazole-MIC ≥ 64 µg/mL and imipenem-MIC ≥ 2 µg/mL or meropenem-MIC ≥ 2 µg/mL, which revealed that Enterobacter cloacae was the largest species detected. Understanding of the epidemiology and the drug-resistant mechanism are needed to prevent the spread of carbapenem-resistant E. cloacae (CREC). METHODS: A retrospective cohort analysis of patients who were positive for CREC from April 2012 to March 2016 at Nagoya University Hospital (a single tertiary hospital in Japan) was performed. Patient information was obtained from electric health records. Molecular epidemiology for CREC isolates was assessed by repetitive-sequence-PCR-based DNA fingerprinting (DiversiLab(®), bioMerieux, France) and multilocus sequencing typing (MLST). Types of carbapenemases were determined by PCR-sequencing method. Clinical backgrounds and outcomes were compared between carbapenemase-producing E. cloacae (CPEC) cases and non-CPEC cases. RESULTS: We identified 41 CREC isolates from 39 patients (19 CPEC isolates in 19 patients). Ten CPEC and 9 non-CPEC isolates were colonization (Table 1). CPEC cases were more likely to have longer hospital stay from admission to positive culture (median 31 days vs. 13.5 days, P = 0.0253) (Table 2) than non-CPEC cases, however, ages, underlying diseases, type of infection and outcomes did not differ significantly. IMP-60 gene was identified in 18 CPEC isolates. Molecular epidemiological study by DiversiLab(®) revealed 4 main CPEC clusters, including isolates detected months apart from different patients (Figure 1). MLST analysis showed 30 CREC isolates belonged to previously reported sequence type (ST). Eighteen CPEC isolates belonged to ST53, 78, 113, and 513, respectively, which were compatible with clusters classified by DiversiLab(®). CONCLUSION: CPEC could be propagated horizontally from patient to patient and possibly by plasmid dissemination. Strict infection control is necessary to prevent the spread of CREC. DISCLOSURES: All authors: No reported disclosures.